2008
DOI: 10.1124/mol.107.044743
|View full text |Cite
|
Sign up to set email alerts
|

AKT Is Activated in an Ataxia-Telangiectasia and Rad3-Related-Dependent Manner in Response to Temozolomide and Confers Protection against Drug-Induced Cell Growth Inhibition

Abstract: The phosphatidylinositol 3-kinase/AKT pathway is activated frequently in human cancer, and it has been implicated in tumor cell proliferation, survival, and chemoresistance. In this study, we addressed the role of AKT in cellular responses to the therapeutic methylating agent temozolomide (TMZ), and we investigated the possible link between TMZ-induced modulation of AKT function and activation of ataxia-telangiectasia and Rad3-related (ATR)-and ataxia telangiectasia mutated (ATM)-dependent signaling pathways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 38 publications
5
73
0
Order By: Relevance
“…Nagane et al (22) and Weller et al (23) showed that up-regulation of either Bcl-2 or EGFR expression in glioma cell lines was correlated with drug resistance and decreased apoptotic response in vitro. Caporali et al demonstrated that Akt was activated in an ataxia telangiectasia and Rad3 related-dependent manner in response to TMZ and conferred protection against druginduced cell growth inhibition (24). These results strongly support the hypothesis that clinical benefits are obtained by combining TMZ with inhibitors of the Akt pathway.…”
Section: Discussionsupporting
confidence: 77%
“…Nagane et al (22) and Weller et al (23) showed that up-regulation of either Bcl-2 or EGFR expression in glioma cell lines was correlated with drug resistance and decreased apoptotic response in vitro. Caporali et al demonstrated that Akt was activated in an ataxia telangiectasia and Rad3 related-dependent manner in response to TMZ and conferred protection against druginduced cell growth inhibition (24). These results strongly support the hypothesis that clinical benefits are obtained by combining TMZ with inhibitors of the Akt pathway.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, mTOR and its associated protein Rictor have been shown to phosphorylate PKB on Ser-473 in Drosophila and human cells (14,46). Recently, it has also been reported that ATR, another member of the PI3K-like kinase, may act as a novel upstream activator of PKB in response to DNA damage induced by O 6 -guanine methylating agents (47). These data suggest that phosphorylation of PKB at Ser-473 is a complex and important regulatory process in cells and further underscore the key role of PKB activation in many physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Importantly, Akt/PKB kinase is one of the targets of both ATM and ATR kinases as well as DNA-PK. [37][38][39] Caffeine has also been shown to inhibit mTOR kinase in vitro at low milimolar concentrations. 30 Moreover, recent reports showed that cellular senescence induced in immortalized epithelial cells by overexpression of p16 and p21, two inhibitors of cyclin-dependent kinases, may be decelerated by a specific mTOR inhibitor rapamycin.…”
Section: Discussionmentioning
confidence: 99%